Research of Mongol graves in Uvur Delger Mountain - Natsag, Batbold; Sanjperlee, Enkhbold; Davaasuren, Mandakh (Studia Archaeologica, 2022)
In 2020, as part of the custom project “Nobility of the Mongolian Empire”, the field research department of the Institute of Archeology of the MAS, in 2020, excavated 8 graves related to the Mongol period in Uvur Delger Mountain in the Sumber Sum area of Govsumber Province. Human and animal bones were found. Based on the study of animal bones, the authors tried to explain the meaning of the anklets found in Mongol graves in connection with the idiom “grandson to hold mouth”. Also, this article discusses the use of horse bones in the burial rituals of that time, and the fact that the practice of horse bones has been handed down since the Bronze Age. Өвөр дэлгэр уулын монгол булшны судалгаа Товчлол. “Монголын эзэнт гүрний язгууртан” захиалгат төслийн хүрээнд ШУА-ийн Археологийн хүрээлэнгийн хээрийн шинжилгээний анги 2020 онд Говьсүмбэр аймгийн Сүмбэр сумын нутагт орших Өвөр дэлгэр ууланд Монголын үед холбогдох 8 булш малтан судалж сумны зэв, төмөр хайч, төмөр илүүр зэрэг олдвор илрүүлснээс гадна булш тус бүрээс хүн, малын яс илэрч олджээ. Зохиогчид малын ясны судалгаанд тулгуурлан Монгол булшинд дагалдуулдаг шагайт чөмөгний учир холбогдлыг “ам барих ач” гэдэг хэлц үгтэй холбон тайлбарлах оролдлого хийсэн байна. Мөн энэ өгүүлэлд тухайн үеийн оршуулгын зан үйлд адууны ясаар тахил үйлдэж байсан талаар авч үзсэн байна. Түлхүүр үгс: Өвөр дэлгэр уул, Монгол булш, малтлага судалгаа, шагайт чөмөг, малын яс